PENGEMBANGAN E-LKPD BERBANTUAN WIZER.ME PADA MATERI KEUNIKAN KEBIASAAN MASYARAKAT DI SEKITARKU - Nida Nur Adiilah; Sukmanasa, Elly; Mulyawati, Yuli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research uses a Research and Development (R&D) approach. The research subjects are 35 fourth-grade students at SDN Sukatani Elementary School in Bogor District, conducted during the second semester of the 2024/2025 academic year. This study uses the ADDIE model (Analysis, Development, Implementation, and Evaluation). Data collection was conducted through observation, interviews, validation tests with media experts, language experts, subject matter experts, and the completion of teacher and student response questionnaires. The validation results by media experts were 96% with the criterion of “Very Suitable,” language experts were 98% with the criterion of “Very Suitable,” subject matter expert 1 by lecturers was 93% with the criterion of “Very Suitable,” and subject matter expert 2 by teachers was 96% with the criterion of “Very Suitable.” The student response questionnaire results were 93% with the category “Very Suitable,” the teacher response questionnaire was 86% with the category “Very Suitable,” and the average N-Gain learning outcome score was 0.70 with the criterion “High.” These results indicate that the development of E-LKPD assisted by Wizer.me on the topic of “Unique Customs of the Community Around Me” is highly suitable for use in the learning process and highly effective in improving student learning outcomes Keywords: E-LKPD, Wizer.me, ADDIE, RnD